2022
DOI: 10.1556/066.2022.00056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the first COVID–19 lockdown on the lifestyle of elementary school children

Abstract: COVID-19 lockdown affects people's daily routine and has an impact on their lifestyle. Recent studies documented associations between body weight changes and children's lifestyle during social isolation. Childhood obesity is associated with a higher risk of COVID-19 severity and mortality. Our aim was to assess the effects of lockdown due to the COVID-19 pandemic on children's sleep, screen time, physical activity, and eating habits. 387 parents of five elementary school students between 16 and 26 June 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…This could be related to the greater pressure exerted by parents staying at home with their children, specifically in the case of younger children [14]. Similar results were found by other researchers [9,11,12,16], who also indicating that snacks were more often eaten as evening or nighttime meals.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This could be related to the greater pressure exerted by parents staying at home with their children, specifically in the case of younger children [14]. Similar results were found by other researchers [9,11,12,16], who also indicating that snacks were more often eaten as evening or nighttime meals.…”
Section: Discussionsupporting
confidence: 81%
“…Respondents argued that it was often skipped before the pandemic due to the morning rush, the need to travel to school, and the accompanying morning emotions. Other authors have also noted an increase in breakfast consumption in families during the COVID-19 pandemic [10,12,16,53]. Some research, however, did not show changes in breakfast consumption [54], and others even indicated a decrease, compared to the pre-pandemic period [55,56], which may indicate a different reference point of the respondents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The pandemic has caused notable shifts in the daily routines of children. These changes include reduced physical activity, increased screen time, and alterations in dietary habits, all of which are consequences of the COVID-19 pandemic (3,4). Research conducted during this period indicates an increase in weight among children and adolescents (5) For girls aged 6-8 years, the cut-off value for the MFR in the 3rd quintile, as determined by the BMI, was found to be ≤0.81, while for girls aged 9-10 years, it was ≤0.78.…”
Section: Introductionmentioning
confidence: 99%